Effectiveness of Differentiated Instruction to Improve Literacy and Numeracy Skills - Aji, Pujo Setyo; Ardjaka , Sugiyono; Julaeha, Siti (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2025)
This research aims to examine the effectiveness of differentiated instruction in improving literacy and numeracy skills of sixth-grade elementary students. A quasi-experimental design involving a control class and an experimental class was employed in Kediri, East Java. A total of 53 students participated, with the experimental group receiving differentiated instruction based on students’ readiness, interest, and learning profiles, while the control group followed conventional teaching. Pre-test and post-test were administered to measure competencies. Results showed significant improvement in both literacy and numeracy skills in the experimental group compared to the control group. Statistical analysis revealed that the experimental group achieved higher mean posttest scores (literacy = 80.1; numeracy = 74.3) than the control group (literacy = 69.1; numeracy = 64.3). Independent sample t-test confirmed significant differences (t[51] = 5.84 for literacy; t[51] = 6.12 for numeracy; p = 0.000 < 0.05). The N-gain values were categorized as moderate (literacy = 0.56; numeracy = 0.52). These findings confirm that differentiated instruction enhances learning outcomes and addresses diverse student needs effectively. The study provides important implications for implementing differentiated learning as part of Kurikulum Merdeka in Indonesian elementary schools.